Determinants of Loyalty in Prasojo Cooperative, Department of Education and Culture, Sukoharjo Regency - Dian Saraswati; Istiatin; Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to determine the simultaneous (simultaneous) or partial effect of the variables of service quality, product variation, trust and satisfaction on customer loyalty of Prasojo Cooperative, Department of Education and Culture of Sukoharjo Regency. This study took place at Prasojo Cooperative, Department of Education and Culture of Sukoharjo Regency. This type of research is a quality or correlational relationship that will explain the asymmetric relationship between the variables studied. The research sample was 80 Prasojo Cooperative customers. Data collection using questionnaires, interviews, observations and documentation. Data analysis techniques using multiple regression tests, F tests, t tests, and determination tests (R2). The results of the study indicate that service quality, product variation, trust and satisfaction simultaneously and partially have a positive and significant effect on customer loyalty of Prasojo Cooperative, the higher the level of service quality, product variation, trust and satisfaction, the higher the customer loyalty of Prasojo Cooperative, and the calculation result of Adjusted R Square (R2) = 0.489, meaning that the contribution of the variables of service quality, product variation, trust and satisfaction to customer loyalty of Prasojo Cooperative is influenced by 48.9% while the remaining 51.1% is influenced by other factors not explained in the study.